Gas phase synthesis of metallic and bimetallic catalyst nanoparticles by rod-to-tube type spark discharge generator. (September 2018) - Ahmad, Saeed; Laiho, Patrik; Zhang, Qiang; Jiang, Hua; Hussain, Aqeel; Liao, Yongping; Ding, Er-Xiong; Wei, Nan; Kauppinen, Esko I.
Abstract: We report a novel design of spark discharge generator which consists of rod and tube electrodes for the gas phase synthesis of catalyst nanoparticles. We synthesized monometallic catalyst particles (Fe, Ni, Cu) and bimetallic particles (Co-Fe, Co-Ni) with the rod-to-tube type spark discharge generator (R-T SDG). Time stability and size distribution of the particles were studied by a scanning mobility particle sizer with an electrometer. We found that R-T SDG maintains a constant size distribution of the nanoparticles for 24 h. These nanoparticles have a geometric mean mobility diameter of 5.17, 5.46, 4.54, 4.90, and 4.72 nm of Fe, Ni, Cu, Co-Fe and Co-Ni, respectively. A high-resolution transmission electron microscope (HRTEM) equipped with X-rays energy dispersive spectrometer (EDS) was used to obtain morphology, composition and structure of the nanoparticles. From HRTEM micrographs, we found separated nanoparticles and small agglomerates (< 8 nm), whereas EDS showed highly pure metallic and bimetallic nanoparticles. As an application of the aerosol produced catalyst nanoparticles, single-walled carbon nanotubes were synthesized using floating catalyst chemical vapor deposition technique with R-T SDG produced iron particles as a catalyst. Highlights: Designed innovative rod-to-tube type spark discharge generator for the gas phase synthesis of nanoparticles. Synthesized monometallic Fe, Ni, Cu and bimetallic Co-Ni, Co-Fe catalyst nanoparticles. Studied effect of nature and flow rate of carrier gas on particle size distribution. Used spark produced iron catalyst particles for the synthesis of single walled carbon nanotubes by FC-CVD method.